PENERAPAN METODE KLASIFIKASI ABC DAN 5S PADA GUDANG TOOLS PT. MESIN ISUZU INDONESIA: Penerapan Metode Klasifikasi ABC dan 5S Pada Gudang Tools PT. Mesin Isuzu Indonesia - Olga Aditya Putra; Indro Prakoso (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
PT.Mesin Isuzu Indonesia manufacturing industry engaged in the automotive sector which produces machinery for Isuzu products as well as several other car parts. The warehouse is a very vital place for every company, the optimal warehouse layout will support the company's production process in meeting production targets because makes it easy to get things. The potential for tool changes can not be avoided and can occur at any time, the search process for the old tool will increase maintenance time so that it is feared that the target wil not be met. This means that the layout of the tool shed must be made optimal so that when engine maintenance occurs the search process for the tool does not take much time. ABC Classification is a method for grouping based on 3 types: fast, medium, and slow. The results of this research are the layout of tools on a shelf based on ABC classification and 5S principles